Two new species of Ochthebius Leach (Coleoptera: Hydraenidae) from Turkey - Ertorun, Nesi̇l; Jäch, Manfred A. (Zootaxa, 2014)
Two new species of Ochthebius Leach (Coleoptera: Hydraenidae) are described from Turkey: O. (s.str.) halophilus (Kırıkkale Province) and O. (Asiobates) arator (Kütahya and Uşak Provinces). The former is the first member of the Ochthebius (s.str.) notabilis species group from Turkey, and the latter belongs to the O. (Asiobates) bicolon group. Both of the new species are characterized by a remarkable aedeagus and are very probably endemic to Turkey.